2018
DOI: 10.1002/adfm.201803130
|View full text |Cite
|
Sign up to set email alerts
|

Composition‐Tuned Wide Bandgap Perovskites: From Grain Engineering to Stability and Performance Improvement

Abstract: Wide bandgap (WB) organic-inorganic hybrid perovskites (OIHPs) with a bandgap ranging between 1.7 and 2.0 eV have shown great potential to improve the efficiency of single-junction silicon or thin-film solar cells by forming a tandem structure with one of these cells or with a narrow bandgap perovskite cell. However, WB-OIHPs suffer from a large opencircuit voltage (V oc ) deficit in photovoltaic devices, which is associated with the phase segregation of the materials under light illumination. In this work the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
120
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 149 publications
(126 citation statements)
references
References 35 publications
3
120
0
3
Order By: Relevance
“…For both 4-T and 2-T Si tandems, a bandgap of ~1.7 to 1.8 eV is expected to yield higher cell voltages ( 21 ), all other things being equal, than the 1.63-eV bandgap material used herein. At present, the high bandgap perovskites show a greater difference between the bandgap and cell open-circuit voltage ( V oc ) than the more optimized lower bandgap compositions ( 7 , 22 , 23 ), mitigating the potential gains in voltage. Layer thicknesses of ~120 and ~50 nm ( 22 ) were used for the organic hole–selective layers (Spiro-OMeTAD and PTAA, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…For both 4-T and 2-T Si tandems, a bandgap of ~1.7 to 1.8 eV is expected to yield higher cell voltages ( 21 ), all other things being equal, than the 1.63-eV bandgap material used herein. At present, the high bandgap perovskites show a greater difference between the bandgap and cell open-circuit voltage ( V oc ) than the more optimized lower bandgap compositions ( 7 , 22 , 23 ), mitigating the potential gains in voltage. Layer thicknesses of ~120 and ~50 nm ( 22 ) were used for the organic hole–selective layers (Spiro-OMeTAD and PTAA, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Reproduced with permission. [100] Copyright 2018, Wiley-VCH. c) PL intensity change over time under different atmospheric conditions.…”
Section: Light Soaking Effects Ion Migration and Sample Degradationmentioning
confidence: 99%
“…[99] Moreover, via continuous PL monitoring they found that halide segregation can be suppressed by controlling the light distribution or the defect density in the film. [99] Zhou et al [100] compared PL intensity change over time in wide-bandgap Cs 0.17 FA 0.83 PbI 3-x Br x (x = 0.8, 1.2, 1.5, and 1.8)…”
Section: Light Soaking Effects Ion Migration and Sample Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…(b) Reprinted with permission from [62]. Copyright 2017 Elsevier Inc. (c) prepared from data published in[53,57,69,72,104,105].…”
mentioning
confidence: 99%